Where is Environmental Issue Integration in Science Education Heading? Bibliometric Evidence on Emerging Research Frontiers - Kurdiati, Lintang Auliya (Jurnal Paedagogy, 2026)
This study aims to analyze the integration of environmental issues in science education by systematically mapping research evolution and identifying emerging trends between 2015 and 2025. Employing a Systematic Literature Network Analysis (SLNA), the study combines a PRISMA-guided systematic literature review with bibliometric network analysis using Biblioshiny and VOSviewer. Data were retrieved from Scopus through a refined search strategy limited to peer-reviewed, open-access journal articles in the social sciences domain. Following PRISMA-based screening, 63 articles were analyzed to identify publication trends, influential contributors, thematic structures, and emerging research directions. The results reveal a notable increase in publication output after 2019 and the formation of five dominant thematic clusters: science education and literacy, sustainability education, socio-scientific reasoning, teacher professional development, and STEM integration. Keyword co-occurrence and density analyses indicate growing convergence around sustainability, inquiry-based learning, and ethical reasoning, highlighting these areas as key research frontiers. These findings emphasize the importance of integrating sustainability competencies into science curricula and strengthening teacher professional development to address environmental socio-scientific issues. Future pedagogical approaches should focus on inquiry-based STEM learning, socio-scientific issues (SSI)–based instruction, and ethics-oriented environmental reasoning to enhance students’ critical thinking and responsible decision-making regarding environmental challenges.